The effectiveness of Communication Model in Teaching Wortshatz SCMR Berlo - Saud, Syukur; Usman, Misnawaty; Saleh, Nurming (Indonesian Journal of Educational Studies, 2013)
The purpose of this research is to implement a model of Communication SMCR Berlo an effort to improve the mastery of German vocabulary (wortschatz) high school students in the city of Makassar. The design used in this study is one group pretest-posttest design. The technique of collecting data through vocabulary tests and questionnaires. The data obtained in this study were analyzed by descriptive quantitative t-test using SPSS 15.0 software program. The data obtained from the questionnaire were analyzed by descriptive narrative. The results show an increase in category seeing, hearing, touching, and smelling. Thus, the model inferred Berlo SCMR effective communication to enhance the students' mastery of the German language vocabulary